Personally oriented teaching as one of the ways of forming subject competences of future teachers of philological specialties (Pedagogy of Higher and Secondary Education, 2012)
Shtelmakh H. B. Personally oriented teaching as one of the ways of forming subject competences of future teachers of philological specialties.The article deals with the preference of the personal and orientative te aching during the process of pedagogical training. The functions of pedagogical communicating are investigated in the article.
Keywords: the personal and orientative teaching; creative personality